Constraints on convergence: hydrophobic hind legs allow some male pollinator fig wasps early access to submerged females. Issue 13 (11th April 2017) - Rodriguez, Lillian J.; Young, Freya; Rasplus, Jean-Yves; Kjellberg, Finn; Compton, Stephen G.
ABSTRACT: Pollinator fig wasps (Hymenoptera: Agaonidae) display numerous adaptations linked to their obligate association with fig trees ( Ficus ). Ceratosolen fig wasps pollinate figs that often fill temporarily with liquid, and one clade has males with unusually long hind legs. We investigated their morphology and behaviour. Scanning electron microscopy (SEM) revealed that the cuticle of their hind legs is highly modified and covered with numerous hydrophobic setae and microtrichia that can prevent blockage of the wasps' large propodeal spiracles by liquids. In deep liquid, the males floated on the surface, but when only a thin layer of liquid was present, the legs allowed males to access females without the risk of drowning. Access to females was facilitated by an air bubble that forms between the hind legs and maintains a column of air between the spiracles and the centre of the figs. Sexual selection should favour males that can gain earlier access to mates, and the modified legs represent an adaptation to achieve this. Convergent adaptations are known in some unrelated non-pollinating fig wasps that develop in similar liquid-filled figs, but these species have enlarged hydrophobic peritremata at the ends of their metasoma to protect the spiracles located there. Unlike non-pollinating fig wasps, pollinator males need to insert their metasoma deep into females' galls during mating. This difference in mating behaviour has constrained the extent of convergence.